Changing in a GIF (Graphics Interchange Format): Innovations in Before and After Photography. Issue 3 (May 2020) - Akella, Sruti S.; Goldstein, Tova; Kumar, Shaina; Patel, Parth; Heo, Moonseong; Barmettler, Anne
Abstract : Purpose: Before and after images are an important part of aesthetic counseling, but no studies have examined ways to optimize change detection through the layout of displayed images. This study compares 3 different image layouts to determine which presentation style improves perception of postprocedure changes. Methods: In this prospective, randomized study, participants viewed sequential images of patients who either had or had not undergone upper eyelid blepharoptosis repair or blepharoplasty ("change" and "no-change, " respectively). These paired images were randomly presented in 1 of 3 formats: side-by-side, up-and-down, or alternation flicker (in which 2 images are superimposed and alternated in a graphics interchange format). Participants were asked if a procedure had been performed based on the 2 photographs. Paired t tests were used to compare response times and change detection rates between individual-level pairs of presentation modes. Results: Of 299 recruited patients, 286 completed the study. Rate of change detection trended toward increased sensitivity for alternation flicker over static images. This became statistically significant for patients less than 45 years old. Detection rates did not differ significantly between the 2 static layouts (side-by-side and up-and down). Conclusions: Enhancing and customizing aesthetics counseling for different ages can improve patient understanding, expectations, and advertising. When using static photography, the layout, whether side-by-side or up-and-down, can be chosen to fit the mode of presentation with no statistically significant difference. To optimize detection of changes in before and after photography in a demographic less than 45 years old, the animated, alternation flicker format was statistically significantly more effective. Abstract : Alternation flicker or graphics interchange format technology is an underutilized, more effective way to highlight subtle changes after cosmetic surgery and may be ideal for use in websites or social media accounts.Supplemental Digital Content is available in the text.